Ancient Worlds in Digital Culture - Clivaz, Claire; Dilley , Paul; Hamidović, David (Digital Biblical Studies, 2016)
The volume presents a selection of research projects in Digital Humanities applied to the "Biblical Studies" in the widest sense and context. Taken as a whole, the volume restitutes the merging Digital Culture at the beginning of the 21st century.